2015
DOI: 10.1097/ico.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Human Growth Hormone Promotes Corneal Epithelial Cell Migration in Vitro

Abstract: Purpose Corneal wound healing is a highly regulated process that requires the proliferation and migration of epithelial cells and interactions between epithelial cells and stromal fibroblasts. Compounds that can be applied topically to the ocular surface and that have the capability of activating corneal epithelial cells to proliferate and/or migrate would be useful to promote corneal wound healing. We hypothesize that human growth hormone (HGH) will activate Signal Transducer and Activators of Transcription-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Moreover, recent cellular mechanistic data and in vivo data have confirmed the ability of rHGH to stimulate and morphologically activate corneal epithelial stem cells to migrate. 36,37 A pilot study has shown excellent safety and tolerability for this crosslinked CMHA-S when delivered subconjunctivally. 38 In terms of drug delivery, the ability to maintain therapeutic agents, particularly proteins, in a bioactive state during formulation and controlled release is an important capability of this HA polymer technology; this is particularly important for achieving multiday release of expensive large molecules.…”
Section: Translational Experience To Datementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent cellular mechanistic data and in vivo data have confirmed the ability of rHGH to stimulate and morphologically activate corneal epithelial stem cells to migrate. 36,37 A pilot study has shown excellent safety and tolerability for this crosslinked CMHA-S when delivered subconjunctivally. 38 In terms of drug delivery, the ability to maintain therapeutic agents, particularly proteins, in a bioactive state during formulation and controlled release is an important capability of this HA polymer technology; this is particularly important for achieving multiday release of expensive large molecules.…”
Section: Translational Experience To Datementioning
confidence: 99%
“…30 In cell culture and in animal models of delayed wound healing, the data show that delivery of rHGH locally from these CMHA-S films have the potential to treat these more recalcitrant cases. 30,36 The rationale for the choice of rHGH was based on the existing data for the role of rHGH in wound healing systemically. Moreover, recent cellular mechanistic data and in vivo data have confirmed the ability of rHGH to stimulate and morphologically activate corneal epithelial stem cells to migrate.…”
Section: Translational Experience To Datementioning
confidence: 99%
“…We hypothesize that HGH can promote corneal wound healing and that it does so by activating phospho-STAT5 ( p-STAT5 ) signaling and promoting corneal epithelial and fibroblast proliferation and/or migration. 91 To test this hypothesis, we conducted an in vitro study on cell signaling, proliferation, and migration, using an immortalized human corneal epithelial cell line (abbreviated as epithelial cells) and primary human corneal fibroblasts (abbreviated as fibroblasts). 91 We found a dose-dependent increase in p-STAT5 in response to HGH treatment in both the epithelial cells and fibroblasts.…”
Section: Treatment Of Persistent Corneal Epithelial Defectsmentioning
confidence: 99%
“…91 To test this hypothesis, we conducted an in vitro study on cell signaling, proliferation, and migration, using an immortalized human corneal epithelial cell line (abbreviated as epithelial cells) and primary human corneal fibroblasts (abbreviated as fibroblasts). 91 We found a dose-dependent increase in p-STAT5 in response to HGH treatment in both the epithelial cells and fibroblasts. Further, we observed increased wound closure rate in a co-culture system of the epithelial cells and fibroblasts with two methods of co-culturing.…”
Section: Treatment Of Persistent Corneal Epithelial Defectsmentioning
confidence: 99%
“…There was no significant difference between groups (p>0.05). Previous studies observed IGF-1 increases re-epitelization by keratinocyte migration, collagen deposition by fibroblast proliferation, and granulation tissue by neovascularization [10][11][12] .…”
Section: Histological Analysismentioning
confidence: 99%